2005
DOI: 10.1042/bj20050798
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a c-Jun-responsive module in the 5′-flank of the human CYP2J2 gene that regulates transactivation

Abstract: The human cytochrome P450 2J2 (CYP2J2) generates cytoprotective epoxyeicosatrienoic acids from arachidonic acid. Expression of CYP2J2 is decreased in hypoxia, and the resultant decrease in CYP2J2-derived epoxyeicosanoids may contribute to the pathogenesis of cardiac ischaemia. Recent studies have indicated that AP-1 (activator protein-1) regulates CYP2J2 expression in normoxia and hypoxia. Down-regulation of CYP2J2 in hypoxic HepG2 cells was closely associated with the up-regulation of c-fos and transient tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…c-Jun has been shown previously to activate the human CYP2J2 gene (Marden and Murray, 2005). Consistent with previous reports (Yu et al, 1997;Yuan et al, 2006), c-Jun and Nrf2 mRNAs were both increased in HepG2 cells by treatment with BHA (100 M) for 6 and 24 h (P Ͻ 0.05; Fig.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…c-Jun has been shown previously to activate the human CYP2J2 gene (Marden and Murray, 2005). Consistent with previous reports (Yu et al, 1997;Yuan et al, 2006), c-Jun and Nrf2 mRNAs were both increased in HepG2 cells by treatment with BHA (100 M) for 6 and 24 h (P Ͻ 0.05; Fig.…”
Section: Resultssupporting
confidence: 92%
“…The CYP2J2-luciferase reporter constructs p2J2(Ϫ2341/ϩ98), p2J2(Ϫ1228/ϩ98), p2J2(Ϫ152/ϩ98), p2J2(Ϫ122/ϩ98), and p2J2(Ϫ82/ϩ98) were described previously (Marden et al, 2003;Marden and Murray, 2005). The construct p2J2(Ϫ152/ ϩ98; mtϪ105/Ϫ88), containing the mutagenized region Ϫ105/Ϫ88 was generated from p2J2(Ϫ152/ϩ98) using the QuikChange Site-Directed Mutagenesis Kit (Stratagene, Willoughby, NSW, Australia); oligonucleotide sequences are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent investigations have suggested that upregulation of this enzyme, probably through a c-Jun-responsive module, promotes the neoplastic phenotype of carcinoma cells and may be involved in the pathogenesis of a variety of human cancers (Jiang et al, 2005;Marden and Murray, 2005). However, CYP2J2 can also metabolize a number of xenobiotics, including the antihistamine drugs ebastine (Hashizume et al, 2002) and astemizole (Matsumoto et al, 2002), contributing to their presystemic elimination in the small intestine.…”
mentioning
confidence: 99%
“…These combined data demonstrate a potentially important link between Notch1, Notch ligands and FABP7 in malignant glioma. This is important as Jagged-1 has previously been shown to play a role in the activation of the transcription factor Activator Protein 1 (AP-1), which in turn regulates the expression of proteins involved in AA and DHA metabolism such as cyclooxygenase-2 (COX-2) and cytochrome P450 2J2 (CYP2J2) [71][72][73][74]. Thus, Notch and/or its ligands may contribute to the deregulation of lipid metabolism in malignant glioma.…”
Section: Fabp7 and Its Transcriptional Regulatorsmentioning
confidence: 99%